Interaction between orthographic and graphomotor constraints in learning to write. (August 2022) - Danna, Jérémy; Longcamp, Marieke; Nalborczyk, Ladislas; Velay, Jean-Luc; Commengé, Claire; Jover, Marianne
Abstract: We investigated the combined effects of orthographic and graphomotor constraints as a function of handwriting proficiency in children. Twenty-four first graders, 20 third graders, and 21 fifth graders wrote single five-letter words in cursive writing on a sheet of paper affixed to a digitizing tablet. The words were chosen according to two orthographic constraints, namely their lexical frequency and the graphemic complexity of the last three letters, and one graphomotor constraint resulting from the motor difficulty of tracing the first letter. In addition to massive improvements of handwriting with grade, the results revealed, in the youngest group only, an interaction between first-letter difficulty and lexical frequency. This finding suggests that, before handwriting movement becomes automated, the cognitive resources needed for retrieving word spelling interferes with motor processing while writing a difficult letter. When students start learning to write, they are particularly sensitive to the combination of orthographic and graphomotor constraints. Highlights: Handwriting of 1st graders is influenced by both orthographic and motor constraints. Motor and spelling processes interact from the beginning of handwriting acquisition. This calls into question the relevance of evaluating them separately.